Recognition of the rights of domestic workers in India: challenges and the way forward - Mahanta, Upasana; Gupta, Indranath(ed.) (Singapore Springer, 2019)
This book brings together a set of contributions that examine the complexities associated with domestic work by highlighting not only the legal issues but also exploring the social, psycho-social, economic, and cultural dimensions of domestic work. The book aims to ignite a collective effort towards ensuring decent work for domestic workers and facilitate a public debate on their rights. It includes discussions on the issue of social justice with special emphasis on invisibilization and undervaluation of domestic work, feminization of domestic work, and recognizes the rights of domestic workers as human rights. The issues covered in this book bridge the gap between legal and social dimensions of domestic work and address the discrimination faced by domestic workers in a holistic manner. Given its scope, the book would appeal to both academics (law as well as social science) and non-academics. It will be a useful tool for teachers, students, practitioners, policy-makers and civil society organizations working for the unorganized sector.
Keywords: Household employees--Legal status, laws, etc; Social justice